(untitled) (Olhares, 2025)
This article aims to present the scenic dramaturgy Fragmentos as a theatrical text. Text composed from the correlation of materials from different disciplines and arts that was configured in the show Fragmentos, a production of Teatro Cais 21 conceived and premiered by me in March 2023, in Palmela, Portugal. And it presents the creative path reflecting on the concepts “director as playwright”, “material” and “chorality”. This work is part of the research project Field of Vision: chorality and other bodies” awarded by FAPESP as a Research Scholarship Abroad (BPE).